# Im which shows the following expression after the negative exponents have been eliminated? a^ 3 b^

###### Question:

which shows the following expression after the negative exponents have been eliminated? a^ 3 b^ -2 ab^ -4 ,a =/0,b b=/0

(a ^ 3 * b ^ (- 4))/(a * b ^ (- 2))

ab^ 4 /a^ 3 b^ 2

- (a ^ 3 * b ^ 4)/(a * b ^ 2)

(a ^ 3 * b ^ 4)/(a * b ^ 2)

## Answers

x = 2

step-by-step explanation:

if sr parallel to ba then the sides bc and ac are in proportion, that is

[tex]\frac{sb}{cs}[/tex] = [tex]\frac{ra}{cr}[/tex] ← substitute values

[tex]\frac{4x+1}{2x}[/tex] = [tex]\frac{13.5}{6}[/tex] ( cross- multiply )

27x = 6(4x + 1)

27x = 24x + 6 ( subtract 24x from both sides )

3x = 6 ( divide both sides by 3 )

x = 2

umm im not really sure because i never had to do this

step-by-step explanation:

a) at most means it can cost $12 or less

so the inequality sign would be ≤

you would then need to multiply the number of toppings by the 0.35 for each one and add it to the cost of the cheese pizza.

the equation would be 9.99 + 0.35x ≤ 12

b) using the above equation:

9.99 + 0.35x ≤ 12

subtract 9.99 from each side:

0.35x ≤2.01

divide both sides by 0.35:

x ≤ 2.01 / 0.35

x ≤5.74

at most you could have 5 toppings.

the 5 topping pizza would cost: 0.35 x 5 = 1.75 + 9.99 = $11.74

choice b

step-by-step explanation:

f(x) = 88x^2 -264x + 300

the line of symmetry of a parabola is defined by

h = -b/2a

where ax^2 +bx+c=0

so

h = - -264/ (2*88)

h = 3/2

so x = 1.5